Otoritas Keagamaan dan Tata Kelola Budaya dalam Hukum Publik Islam: Studi Fiqh Siyasah tentang Regulasi Konser Musik di Aceh - Sutrisno Sutrisno; Shofiatun Nikmah; Risma Hikmawati; Aty Munshihah; Wahid Syafruddin (Universitas Islam Negeri Antasari Banjarmasin, 2025)
The prohibition of music concerts in Aceh over the past two decades of the post-conflict period has shown an increasingly consolidated trend alongside the deepening institutionalization of Islamic law in the public sphere. This phenomenon reflects a process of negotiation that is not always harmonious between religious authority and contemporary cultural expression often culminating in the cancellation and prohibition of music concerts through administrative mechanisms. This study examines the fiqh siyasah foundations underlying the construction of the Aceh Ulama Consultative Council (MPU) Fatwa No. 12 of 2013 and evaluates the implications of its implementation for governance practices in Aceh. Employing a juridical-normative method with a descriptive-analytical approach, the study analyzes key legal sources underpinning the prohibition of music concerts, including MPU fatwas, regional government circular letters, and classical as well as contemporary fiqh siyasah literature. The findings indicate that MPU Fatwa No. 12/2013 is formulated within the framework of fiqh siyasah through the approaches of siyÄsah sharâ€˜iyyah and maá¹£laá¸¥ah mursalah, functioning primarily as a moral-religious guideline for regulating arts and entertainment in Aceh.However, when such a fatwa is translated into regional policy in the absence of a formal qanun and balanced public deliberation mechanisms, its function shifts from an ethical norm to an instrument of symbolic control over cultural space, thereby constraining the plurality of contemporary cultural expressions. This study recommends the formulation of a specific qanun regulating Islamic arts and culture through a participatory, inclusive, and transparent legislative process, ensuring that shariabased policies remain responsive to the evolving cultural expressions of society